Risk management practices in tourism industry - a case study of resort management / Nur Rahifah Amirudin, Anuar Nawawi and Ahmad Saiful Azlin Puteh Salin. - Amirudin, Nur Rahifah; Nawawi, Anuar; Puteh Salin, Ahmad Saiful Azlin (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2017)
The purpose of this research was to identify the risks factors associated with the operation of a resort and the risk management techniques used to reduce the risks. One resort was selected as the case study and document analysis and observation were used as data collection methods. This study found that the risks can be managed through the right combination of risk management techniques. Despite weak monitoring activities, incomplete operating procedures, and inferior attitude by the workforce seems to impact the management of the resort, fast and intelligent response may be able to overcome the situation and prevent the worst possible outcomes.